The Clinical Characters of Congenital Choledochal Cysts in Perinatal Patients: A Retrospective Analysis in a Single Institution - Tang, Weitao; Dong, Kuiran; Liu, Gongbao; Cui, Ximao; Zheng, Shan (American Journal of Perinatology, 2015)
Object We aimed to investigate the clinical characters of congenital choledochal cysts (CC) in perinatal patients and to determine the most suitable time for their management.Study Design We retrospectively analyzed all the data of patients with CC in our hospital between 2003 and 2013. Clinical characteristics during the perinatal, infancy, and childhood periods were examined.Results A total of 216 cases were analyzed, including 12, 39, and 165 patients in their perinatal, infancy, and childhood periods, respectively. The incidence of abdominal pain and jaundice in the perinatal group was lower than that in other groups (p < 0.0001; p = 0.001). The incidence of abnormal inflammatory markers and liver function in perinatal cases was lower than in the other cases (p = 0.012; p = 0.002). The receiver-operating characteristic curves for liver function indicated that the cut-off point for age at which liver damage was found was 120 days. Of the 12 perinatal cases, there were no significant differences, with regards to operative time and hospital stay, between open and laparoscopic surgical approaches (p = 0.164; p = 0.722).Conclusion Abdominal pain, jaundice, inflammatory markers, and liver function in perinatal patients with CC are better than in the infancy and childhood groups. We recommend surgical treatment before 120 days of age.
Keywords: congenital choledochal cyst; liver function; perinatal; laparoscopic surgery